Template Synthesis of Ni Nanowires: Characterization and Modelling - Nurhanis Sofiah, Abd Ghafar; Ulakanathan, S.; Samykano, Mahendran; K., Kadirgama; Hussein, A. M.; Ngui, Wai Keng (Akademi Baru, 2020)
Template-assisted electrochemical deposition is a straight forward approach for the synthesis of 1D nanostructures (e.g., nanowire, nanorod, and nanobelt) with controllable morphology. This approach is suitable for mass production as it works at ambient pressure and temperature with the properties of synthesized 1D nanostructures being influenced by synthesis conditions during the electrochemical deposition process. This work aims to investigate the influence of stabilizing agent concentration and heating temperature towards the physical behavior of Nickel (Ni) nanowires synthesized via a template-assisted electrochemical deposition approach. In this research, the electrolyte bath was prepared in three different concentrations of the stabilizing agent (6 g/L, 40 g/L and 70 g/L), and the deposition bath temperature used was 30°C, 70°C, and 110°C respectively. The elemental composition was determined using Energy Dispersive X-ray (EDX) analysis to investigate the percentage of pure Ni element in the synthesized nanowires. The diameter, surface texture, and growth length of the synthesized Ni nanowires were characterized using Field Emission Scanning Electron Microscope (FESEM). X-ray diffractions (XRD) was used for crystal size and crystal orientation analysis. Additionally, the mechanical properties of Ni nanowires were extracted via molecular dynamic simulation. Growth length of Ni nanowires found to be significantly improved as the heating temperature increased, but it decreased when stabilizer agent concentration is high. The diffraction patterns for all synthesis conditions exhibited the synthesis Ni nanowires are polycrystalline as the crystalline planes with Miller indices of 111, 200, and 220. All the investigated nanowires showed ductile failure behavior, a typical behavior at larger length scales of Ni.